The Role of Visual Storytelling in Enhancing Disaster Risk Knowledge: Developing Digital Comics for Landslide Mitigation Education - Faisal Amin; Muhammad Saiful Bahri (CV Bumi Spasial, 2024)
Learning media serve as a tool to convey information in the learning process. Various forms of learning media have been proven to affect the interest and motivation of students to support the learning process. Digital comics, as a form of learning media, have the potential to enhance students' understanding and engagement by presenting information through storylines and visually appealing illustrations. This research aims to produce digital comic learning media on landslide disaster mitigation material entitled “Landslide Alert” for XI social studies class students in high school. The developed digital comic will cover topics such as understanding landslides, causal factors, impacts, types of landslides, and disaster mitigation efforts, providing a comprehensive overview for students. This research applied the ADDIE development model, focusing on the initial phases of Analysis, Design, and Development phase to create the foundational elements of the learning media. This research was tested on students in class XI 10 of State Senior High School 1 Kencong. The validation test of media experts obtained results of 97.06% and material experts of 75% by obtaining an overall average percentage of 86.72% including in the very feasible category. The trial on students obtained a percentage of 85.36%. Based on the development research, digital comic learning media for landslide disaster mitigation material with the title